Clinicopathological and molecular features of sporadic colorectal cancers with DNA _x000D_ mismatch repair deficiency: A single center experience - (:unkn) unknown (My University, 2020)
DNA mismatch repair (MMR) proteins may play an important role in colorectal carcinogenesis. In our study, the clinicopathological features of defective MMR in sporadic colorectal adenocarcinomas (CRCs) cases were examined. This is a retrospective study, 457 consecutive cases of colorectal carcinoma with immunohistochemical (IHC) studies for DNA MMR were included.The immunohistochemically (IHC) MMR results of 457 cases were; nuclear expression was intact (proficient, pMMR) in 401 (87.7%) cases and loss of nuclear expression (deficient, dMMR) was found in 56 cases (12.3%). High probability of Lynch syndrome ratio was 2.4% (11/457) in all cases. The loss of PMS2 was predominantly detected in dMMRcases (78.6%). Seventy eight percent of dMMR tumors were located in the proximal colon. In dMMR tumors, prominent peritumoral lymphoid aggregates (LAs) (85.7%) and tumor-infiltrating lymphocytes (TILs) (78.6%) were observed. Among 56 colorectal cancers, we observed expanding /pushing growth pattern in 41 tumors (73.2%), and infiltrative growth pattern in 15 cancers (16.8%). Medullary, mucinous and signet ring cell carcinomas were observed in approximately half of the cases, but there was no statistically significant relationship. Eighty nine percent of dMMR cases had advanced pathologic tumor stage (pT3 or pT4), and this rate was 82.5% in pMMR cases. The average number of positive lymph nodes in cases with dMMR was higher than in pMMR. KRAS mutations were detected in 7.2% (4/13) patients and 14.3% (8/13) patients with MLH1 promoter methylation was observed. Seventy percent of patients with dMMR were alive (n=44) and the mean age of the patients who died was higher. A statistically significant relationship was found between the patients who died and the mean age of surviving patients (p = 0.036). We conclude that the dMMR patients constitutes have a number of distinctive clinicopathological features subtype of sporadic CRC. The overall frequency of defective MMR in colorectal carcinoma cases was found to be Turkish population similar to western studies. dMMR in CRCs were more likely to be of advanced pathologic tumor stage to have a mucinous tumor component and positive LN to show PMS2 loss and to harbour higher numbers of both peritumoral LAs and TILs. They were also more likely to be proximal colon and to occur in male.